Affect in designing for sustainability in human factors and ergonomics. (1st January 2012) - Thatcher, Andrew
Affective human factors design attempts to incorporate a user's feelings and emotions towards a product or system into the design process. In this article, the principles of affective human factors design are applied to the design of products and systems that have sustainability as their aim. Many sustainable products and systems have struggled to gain widespread adoption and use. This article presents a framework to show how affective design might be used as a tool to facilitate the adoption and early engagement with designs for sustainability. The three elements (design for functional balance, design for early engagement and design for aspirational ideology) depict the three points at which affective design tools might be leveraged to encourage more sustainable product purchases and thereby more sustainable behaviours. Examples of sustainable products and systems are provided to illustrate the framework. The article concludes with a set of limitations and cautionary notes.